The Road Transport Inspection role in reducing traffic accidents in Poland - Wieteska, Stanisław (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Road Transport Inspection (ITD) was established in 2001. Its aim is to increase traffic safety. This article aims to answer the question to what extent the appointment of ITD. contributes to improving road safety in Poland. In the article, in addition to discussion the objectives of the organization and scale of accidents involving heavy vehicles, we discuss quantitative status checks carried out. We are observing the period 2005–2012. The article shows that with strong administrative decisions and criminal proceedings, the number of accidents and their consequences involving heavy duty motor vehicles is reduced.